Multicultural Values in Tthe Simbur Cahaya Malay Customary Law - Hermansyah, Hermansyah; Adil, Muhammad; Syawaludin, Mohammad; Ibrahim, Duski; Rahman, Pathur (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to analyze the construction of multicultural values within the Malay customary law tradition through the Simbur Cahaya Law, which has developed within the Malay community of Palembang in South Sumatra. The Simbur Cahaya Law is a customary legal system that serves as a normative guideline for regulating social life and reflects the integration of customary values, social ethics, and religious traditions within the community. This study employs a qualitative approach using a normative-historical analysis of the text of the Simbur Cahaya Law and relevant literature. Data were collected through document studies and literature analysis, then analyzed thematically through a process of data reduction, value categorization, and interpretation of the socio-cultural meanings contained within these customary legal norms. The research findings indicate that the Simbur Cahaya Law contains a number of multicultural values that serve as the foundation of social order in the community, including social justice, communal solidarity, deliberation, respect for diversity, and the balance of relationships between humans, society, and the environment. The novelty of this study lies in mapping the construction of multicultural values within the Simbur Cahaya Law as a social ethical system rooted in local wisdom that plays a role in maintaining social harmony within the Malay community. This study recommends strengthening research on customary law and local wisdom as relevant sources of multicultural values to reinforce social cohesion and the preservation of cultural identity amidst contemporary social dynamics.